EVALUATION OF CAROTID INTIMA-MEDIA THICKNESS AS AN EARLY PREDICTOR OF ATHEROSCLEROSIS IN RHEUMATOID ARTHRITIS PATIENTS (World Bulletin of Public Health, 2021)
Cardiovascular disease (CVD) is one of the leading causes of death and disability worldwide. Rheumatoid arthritis is a common chronic connective tissue disease in adults and children, which leads to destruction of symmetrical joints. According to the European Society of Cardiology, "...over 4 million people die each year from CVDs, of which 1.4 million under 75 years old, accounting for 45% of all deaths...". According to major research centres, cardiovascular mortality (CVD) is more common in patients with rheumatoid arthritis (RA) than in the general population
Keywords: Rheumatoid Arthritis; Cardiovascular Risk; Prevention; Atherosclerotic Lesions